CONGRUENT NON-UNIFORM ANTENNA ARRAYS - RAY GARY (2016)
Systems, methods, and apparatus for forming an antenna array are disclosed. In one or more embodiments, the disclosed method involves determining at least one coprime moduli set based upon a differential phase gain requirement and a differential phase range requirement for the antenna array. The method further involves producing at least one configuration for relative spacing of antenna elements of the antenna array by using at least one coprime moduli set. Also, the method involves choosing one of configurations for the antenna array to employ by evaluating a resultant gain and an unambiguous angle of arrival (AOA) for each of the configurations. Further, the method involves determining the absolute spacing of the antenna elements of the antenna array for the chosen configuration for the antenna array according to a wavelength requirement for the antenna array.